Nutritional strategies for nursery and growing-finishing pigs: mineral nutrition and feed ingredients to optimize growth performance. - Porcel de Peralta, Tomas (My University, 2026)
This thesis contains three chapters that include: 1) evaluating the effects of modified corn protein (MCP) products on growth performance and fecal dry matter (DM) of nursery pigs; 2) evaluating the effects of increasing standardized total tract digestible phosphorus (STTD P) on growth performance, bone ash, and carcass characteristics of Duroc-sired (PIC 800) pigs; and 3) evaluating the effects of added dietary iodine concentration and feeding duration on growth performance and thyroid hormone status of nursery and wean-to-finish pigs. Chapter 1 utilized 4,420 pigs in two experiments to evaluate three MCP products as replacements for specialty animal and soy protein sources. Increasing MCP inclusion resulted in a dose-dependent reduction in growth performance, particularly gain-to-feed ratio (G:F) and early post-weaning average daily gain (ADG). Despite these negative effects on growth, pigs fed MCP 1, 2, and 3 exhibited increased fecal DM, indicating that although high levels of specialty corn proteins may compromise early growth, they offer a practical benefit in formulations where increased fecal DM is desired. Chapter 2 utilized 1,040 pigs in a 136-d experiment to validate STTD P requirement estimates for Duroc-sired (PIC 800) pigs fed 82 to 110% of current PIC recommendations. Increasing STTD P linearly increased ADG (maximized at or above 103% of the recommendation) and tended to increase hot carcass weight, whereas G:F was maximized between approximately 90 and 97% of the recommendation, with no effect on bone ash or carcass quality. Chapter 3 utilized 3,700 pigs in four experiments to determine the added iodine concentration and feeding duration that optimize growth performance. Increasing added iodine improved early growth performance, with the greatest response at approximately 12 to 14 mg/kg and elevated circulating thyroxine (T4); feeding 14.3 mg/kg continuously from weaning to approximately 110 kg improved overall G:F compared with feeding it only through the early nursery. In summary, these experiments refine dietary nutrient concentrations to optimize performance under research and commercial conditions, providing data on the effects of modified corn protein products on nursery pig growth performance and fecal DM, the STTD P level that optimizes growth and carcass weight in Duroc-sired pigs, and the added iodine concentration and feeding duration that maximize growth and feed efficiency.
Keywords: Nursery pigs; finishing pigs; minerals; feed ingredients